2005
DOI: 10.1007/bf03018578
|View full text |Cite
|
Sign up to set email alerts
|

Le xénon ne réduit pas les besoins d’opioïdes en chirurgie orthopédique

Abstract: P Pu ur rp po os se e: : Is to test the hypothesis that 70% xenon has a relevant opioid sparing effect compared to a minimum alveolar concentration (MAC)-equivalent combination of N 2 O and desflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Of these, we selected 225 for full‐text review, of which 188 papers were excluded because they did not meet our eligibility criteria. After this process we identified a further 15 papers, reporting on 12 studies , which also required exclusion for not meeting these criteria. Of these 12 studies, six did not include an intervention or comparator relevant to this review , in five studies the depth of anaesthesia differed between study arms [ and two papers reported on the ENIGMA‐2 study , which did not measure AAGA.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, we selected 225 for full‐text review, of which 188 papers were excluded because they did not meet our eligibility criteria. After this process we identified a further 15 papers, reporting on 12 studies , which also required exclusion for not meeting these criteria. Of these 12 studies, six did not include an intervention or comparator relevant to this review , in five studies the depth of anaesthesia differed between study arms [ and two papers reported on the ENIGMA‐2 study , which did not measure AAGA.…”
Section: Resultsmentioning
confidence: 99%
“…31 In the first study 31 (data set I, 'I' for infusion data), 30 patients undergoing orthopaedic surgery were randomly allocated to anaesthesia with 70 vol.% of xenon or 70 vol.% of nitrous oxide plus 2 vol.% of desflurane. Alfentanil was administered by TCI (Stanpump programme, S.L.…”
Section: Methodsmentioning
confidence: 99%
“…To carry out the study where the data of alfentanil infusions were taken 31 Drä ger Medical GmbH, Lü beck, Germany provided a Cicero Anaesthesia Workstation adapted for the administration of xenon. The xenon was generously provided by Messer Griessheim GmbH, Krefeld, Germany.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 142 surgical patients xenon anesthesia was well tolerated except for more nausea and vomiting compared to those randomized to propofol (30). Several other studies in surgical patients reported xenon was well tolerated as an anesthetic (31)(32)(33)(34). In a pilot study of critical care sedation for 8 hours, 21 patients randomized to either propofol or inhaled xenon (9-62 %) had comparable sedation.…”
Section: Introductionmentioning
confidence: 91%